Exploring opportunities for diversification of specialized tobacco farms in the Northwest of Argentina - Chavez Clemente, Maria Daniela (2012)
Tesis para obtener el grado de Doctor Economía Agraria y gestión (PhD), de la Wageningen University, en 2012